2021
DOI: 10.3390/ijerph18042204
|View full text |Cite
|
Sign up to set email alerts
|

Do Different Models Induce Changes in Mortality Indicators? That Is a Key Question for Extending the Lee-Carter Model

Abstract: The parametric model introduced by Lee and Carter in 1992 for modeling mortality rates in the USA was a seminal development in forecasting life expectancies and has been widely used since then. Different extensions of this model, using different hypotheses about the data, constraints on the parameters, and appropriate methods have led to improvements in the model’s fit to historical data and the model’s forecasting of the future. This paper’s main objective is to evaluate if differences between models are refl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…They found that the simplest version has the best forecasting ability for most European countries in the Human Mortality Database (2021). Furthermore, Debón et al (2021) found that the life expectancy of this version of the model has a better response to the financial challenges posed by longevity risk. For these reasons, the model of Lee and Carter (1992) was used.…”
Section: Modelling Dynamic Life Tablesmentioning
confidence: 93%
“…They found that the simplest version has the best forecasting ability for most European countries in the Human Mortality Database (2021). Furthermore, Debón et al (2021) found that the life expectancy of this version of the model has a better response to the financial challenges posed by longevity risk. For these reasons, the model of Lee and Carter (1992) was used.…”
Section: Modelling Dynamic Life Tablesmentioning
confidence: 93%
“…This Special Issue contains 11 contributions from diverse research lines, representing different geographies, such as America, Asia or Europe. Some of them are related to elderly or disabled populations ( [1][2][3][4]), while others present new financial or actuarial proposals ( [5][6][7]) or focus on specific diseases, specific factors of mortality or on general wellbeing ( [8][9][10][11]). All of them apply state-of-the-art tools or develop new methods to visualize and analyse data coming from multiple sources to produce reliable measurements on peoples' health and wellbeing.…”
mentioning
confidence: 99%
“…Ana Debón, Steven Haberman, Francisco Montes and Eduardo Otranto [6] evaluate the use of different mortality models on a set of indicators. All models are variants of the original Lee-Carter model.…”
mentioning
confidence: 99%